2020
DOI: 10.1016/j.ajhg.2020.04.018
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of Function of RIMS2 Causes a Syndromic Congenital Cone-Rod Synaptic Disease with Neurodevelopmental and Pancreatic Involvement

Abstract: Congenital cone-rod synaptic disorder (CRSD), also known as incomplete congenital stationary night blindness (iCSNB), is a non-progressive inherited retinal disease (IRD) characterized by night blindness, photophobia, and nystagmus, and distinctive electroretinographic features. Here, we report bi-allelic RIMS2 variants in seven CRSD-affected individuals from four unrelated families. Apart from CRSD, neurodevelopmental disease was observed in all affected individuals, and abnormal glucose homeostasis was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 53 publications
2
42
0
Order By: Relevance
“…Inner retinal thinning was seen in the three subjects for whom OCT was available, and RNFL thinning was shown in two of them [15]. Whilst the authors advise optic disc and inner retinal changes should be interpreted with caution in the context of myopia, it is noted that none of the cases had high myopia (range: +6.00 to −4.50 D; only three were myopic) [15]. In 1983 Heckenlively et al reported optic disc anomalies (interpreted as representing atrophy, dysplasia, or both) in subjects with CSNB; five had tilted discs with a lack of visible temporal disc tissue, two had dysplastic nerves and three had disc pallor without tilt [81].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Inner retinal thinning was seen in the three subjects for whom OCT was available, and RNFL thinning was shown in two of them [15]. Whilst the authors advise optic disc and inner retinal changes should be interpreted with caution in the context of myopia, it is noted that none of the cases had high myopia (range: +6.00 to −4.50 D; only three were myopic) [15]. In 1983 Heckenlively et al reported optic disc anomalies (interpreted as representing atrophy, dysplasia, or both) in subjects with CSNB; five had tilted discs with a lack of visible temporal disc tissue, two had dysplastic nerves and three had disc pallor without tilt [81].…”
Section: Discussionmentioning
confidence: 95%
“…To date, a few cases in the literature have documented optic disc pallor or atrophy in CACNA1F-related iCSNB [18][19][20] and these reports are limited to the clinical appearance, rather than the graded measurement of optic disc pallor or ganglion cell structural integrity. All seven reported cases of iCSNB associated with RIMS2, a regulator of synaptic membrane exocytosis localized to rod photoreceptors and the outer plexiform layer, from 3 unrelated, ethnically diverse families demonstrated clinically appreciable optic disc pallor [15]. Inner retinal thinning was seen in the three subjects for whom OCT was available, and RNFL thinning was shown in two of them [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ). The most foveal enriched cone photoreceptor gene was RIMS2 , a regulator of synaptic membrane exocytosis that has been implicated in a congenital cone-rod synaptic disorder ( 18 ). Several additional genes implicated in synaptic transmission were enriched in foveal cone photoreceptors, likely reflecting the unique synaptic characteristics of foveal cones.…”
Section: Resultsmentioning
confidence: 99%